Micro-fluidic Integrated Toolkit for Micro-bioreactors and Bio-catalytic Processes. (2017) - Panjan, P.; Virtanen, V.; Sesay, A.M.
Abstract: For true "Lab on a chip" applications, integration of microfluidics and analytical devices need to be realized. Here we report on 2D and 3D fabricated microfluidic "chips" based on unit operations (i.e. mixing, pumping, splitting and sensing) that can be combined and are applied to the cell cultivation of saccharomycescerevisiaeis in a 3D printed milli-bioreactor.